VD_FINDINFO Décision / 2014 / 56 vom 3. Dezember 2013 - VD Tribunal cantonal (2013)
RISQUE DE FUITE, RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 233 CPP (CH)